The Role of Tecar Therapy in the Delayed Onset Muscle Soreness and Functional Recovery: a randomized controlled trial - João Tiago Soares Sanches Samorano Pina (2022)
Introduction: The practice of intense physical exercise without proper conditioning can lead to Delayed Onset Muscle Soreness (DOMS). TECAR therapy, an endogenous thermotherapy, has been included in the spectrum of possible interventions for an early recovery of musculotendinous injuries in athletes. Objective: A randomized controlled trial was conducted to evaluate the efficacy of Tecar Therapy on DOMS and Functional Recovery of 60 athletes. Design: This is a randomized, controlled, double-blind, double-arm clinical trial of treatment, with an allocation ratio 1:1 and framework of superiority. Material and method: This study integrated 60 female volleyball athletes. They were randomly divided into two groups: Tecar group (experimental group, 30 subjects), and control group (30 subjects). All the subjects performed the fatigue protocol, and were evaluated in 5 different moments (Before [M0] and after [M1] the fatigue protocol and Tecar therapy in TG; 24h after the protocol before [M2] and after [M3] Tecar therapy in TG; and 72h after the fatigue protocol [M4]). Results: We found significant improvements in the TECAR therapy group which presented higher pain pressure threshold as well as less muscle soreness compared to the control group, from M2 onwards of the evaluation. Moreover, when individually compared to the initial evaluation moment (M0), the intervention group (GT) recovers in functional performance by the end of 72h (M0 vs M4), in the Single Leg Hop and in three isokinetic parameters in contrast to the control group. Conclusion: TECAR Therapy was shown to be effective in the relief of muscle soreness, from 24h after its application. Similarly, individuals treated with Tecar therapy had better recovery of muscle strength and function at the end of the 72h protocol.